Analisis Kebutuhan E-Modul Pembelajaran Produk Kreatif Dan Kewirausahaan Berbasis Project Based Learning Di Smk Negeri Muara Beliti - Febriana; Supriyanto Supriyanto; Leo Charli (Universitas Hamzanwadi, 2026)
The transformation of vocational education in the industrial revolution 4.0 and society 5.0 eras demands learning that is not only oriented towards mastering technical competencies, but also strengthening communication and collaboration skills as part of 21st-century skills. This study aims to analyze the need for the development of e-modules for creative Products and Entrepreneurship (PKK) learning based on Project Based Learning (pjbl) in promotional materials at SMK Negeri Muara Beliti. The study used a quantitative descriptive approach with a survey method. The research subjects consisted of 25 grade xi students and 2 pkk teachers. The instruments used included a likert scale questionnaire, structured interviews, and documentation studies. Data were analyzed using descriptive statistics and qualitative interpretation. The results showed that 84% of students had difficulty understanding promotional materials in an applicable manner, 89% needed interactive digital learning media, and 92% stated that the pjbl model was effective in improving communication and collaboration through team projects. This needs analysis serves as an empirical basis in the product development stage to improve the quality of entrepreneurship learning in SMK.